RETRACTED: Fertilisers of controlled action as a promising direction of agrochemistry - Rudoy Dmitry; Olshevskaya Anastasiya; Оdabashyan Mary; Prutskov Alexey; Vershinina Anna; Alentsov Egor (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001